Model Kegiatan Microteaching untuk Mengembangkan Keterampilan Melaksanakan Pembelajaran Matematika Berpusat pada Siswa - Putrawangsa, Susilahudin; Syawahid, Muhammad (Jurnal Elemen, 2018)
The current research intends to identify the characteristics of microteaching model that is valid, effective and practical to develop prospective mathematics teachersâ competencies in conducting student-centered instructions. It is a development research carried out according to Educational Design Research. The findings suggests that the characteristics of microteaching model to develop prospective mathematics teachersâ competencies in conducting student-centered instructions are: (1) a microteaching which is carried out in a cycle process consisting of planning, implementing, observing, and evaluating student-centered teaching and learning where each participant acts as a teacher and evaluators in turn. (2) a microteaching that is conducted in form of Peer Microteaching by Self-Study Group where they peer supervise each other (Peer Supervision). (3) a microteaching that has a teacher observation and evaluation protocol that is conducted by themselves (Self-evaluation) and others (Peer Evaluation) and focuses on particular aspects of teacher performance in implementing student-centered instructions those are claimed to important and possible to be refined at the moment (At-the-time improvement). (4) a microteaching which is carried out in a progressive complexity of teaching environment, that is starting from teaching a less complex to a more complex classroom setting.